If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 5t + -2 = 7t + 19 + -4t Reorder the terms: 3 + -2 + 5t = 7t + 19 + -4t Combine like terms: 3 + -2 = 1 1 + 5t = 7t + 19 + -4t Reorder the terms: 1 + 5t = 19 + 7t + -4t Combine like terms: 7t + -4t = 3t 1 + 5t = 19 + 3t Solving 1 + 5t = 19 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 1 + 5t + -3t = 19 + 3t + -3t Combine like terms: 5t + -3t = 2t 1 + 2t = 19 + 3t + -3t Combine like terms: 3t + -3t = 0 1 + 2t = 19 + 0 1 + 2t = 19 Add '-1' to each side of the equation. 1 + -1 + 2t = 19 + -1 Combine like terms: 1 + -1 = 0 0 + 2t = 19 + -1 2t = 19 + -1 Combine like terms: 19 + -1 = 18 2t = 18 Divide each side by '2'. t = 9 Simplifying t = 9
| 8x-14=58 | | -3x-2y=-10 | | 9x+1=12x | | x^2+12+36=5 | | 4(2d+7)=2d+25-3(2d+1) | | 0.1n=8 | | (X+4)+9= | | h^2+5h=225 | | 0.3(30)+0.15x=0.20(30+x) | | n^2-5n+7=0 | | 14x+18=5x+153 | | 32x-2=8x | | 9x+5*(2-x)=3x-(x-15) | | 14x+16=14x-16 | | 111-7x=20x+21 | | 14-10x=109-45x | | 80-5x=13x+22 | | 9a+6ab-(3a)2= | | 6-8x=141-43x | | 0.5(x+10)+0.7x=41 | | z/8-5=-3 | | X-7x-2=0 | | 4x^2+7x-5=0 | | 3x+2y-12=0 | | -7=3c+14 | | 4y-7=y-14 | | p^2-14p-8=0 | | y-14=4y-7 | | 164-5x=6x+21 | | 3x-14+2x+10=180 | | 47-3x=6x+24 | | 4(6x+1)=-2(x-5)+10 |